Underutilised Indigenous Vegetables for Household Dietary Diversity in Southwest Nigeria - Tanimonure, V.A.; Naziri, D.; Codjoe, S.N.; Ayanwale, A.B. (MDPI, 2021)
The diets of many households in developing countries are monotonous and starch-based.Integrating underutilised indigenous vegetables (UIVs) to cropping systems can contribute to bothcrop and dietary diversities, thereby improving rural households’ nutrition and boosting foodsecurity. Therefore, this study established a link between the UIVs’ diversity and the householddietary diversity (HDD) of the UIVs producers in the rural area of Southwest Nigeria. A multistagesampling technique was used to select 191 UIV-producing households in the region. Their HDD wasmeasured based on the 12 unique food groups consumed by households over a 7-day reference periodpreceding the survey, and negative binomial Poisson regression analysis was used to determine therelationship between UIV diversities, other sociodemographic characteristics, and the HDD scoreof the UIV-producing households in the area. The results showed that only about four groups offood contributed greatly to the HDD score. The result of the negative binomial Poisson regressionanalysis showed UIVs diversity as a significant variable that increased the HDD score in the studyarea. Other factors that determined the HDD score of UIV-producing households were the maritalstatus of the household head, farm distance from the home, UIVs land area, off-farm income, UIVsgross margin, per capita food expenditure, and Oyo location. The study concluded that the inclusionof diverse underutilised indigenous vegetables into cropping systems in rural areas and vegetablehome gardening practices in the rural and urban areas of developing countries could alleviate thechallenge of nutrition insecurity.